The influence of coffee clones and postharvest methods on the physical quality of eight clones of local robusta coffee in West Lampung, Indonesia - ANALIANASARI ANALIANASARI; MURHADI MURHADI; SAMSU UDAYANA NURDIN; TANTO P. UTOMO; DIDING SUHANDY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Analianasari, Murhadi M, Nurdin SU, Utomo TP, Suhandy D. 2023. The influence of coffee clones and postharvest methods on the physical quality of eight clones of local robusta coffee in West Lampung, Indonesia. Biodiversitas 24: 5779-5787. One of the qualities of coffee is a physical characteristic that can be seen directly as a determinant of the coffee bean's price. This study consisted of eight clones of robusta coffee picked red, which was processed using the postharvest method (natural, honey, and full wash) with three repetitions, then evaluated based on the physical attributes of the coffee beans (moisture content, weight of 100 coffee beans, length and the width of the coffee beans, the percentage of passing through the Sieve, and the number of coffee bean defects). The results showed that most of the physical quality parameters of clones from local Robusta coffee varieties were carried out using the postharvest method and planted in West Lampung statistically different (P<0.05). The moisture content in naturally processed tugu sari clones had a higher moisture content, but it was not different from the srintil clones in all postharvest processing. All clones can produce specialty (fine) and premium quality coffee beans based on the quality of the physical attributes. However, dry processing (natural and honey) fine coffee clones provide the best quality physical attributes. The findings from this study were that the diversity of cloned robusta coffee with various postharvest methods provides information that indicators of local genetic diversity had different physical attributes, but more significant and repeated experiments are needed to obtain accurate results.